A CLINICAL CASE OF HOSPITAL-ACQUIRED PNEUMONIA CAUSED BY KLEBSIELLA PNEUMONIA, DUE TO CONTACT WITH A FAMILY MEMBER - N.D. Gerasymenko; N.I. Digtiar (Проблеми екології та медицини)
The problem of morbidity and mortality due to infectious lesions of the respiratory tract, in particular nosocomial pneumonia, remain one of the most pressing problems of modern medicine. Nosocomial pneumonia ranks 3rd among all infectious diseases that a patient can contract at a medical institution after urinary and wound inflammation and it is characterized by high mortality. Nosocomial pneumonia is provoked by antibiotic-resistant microorganisms; in the intensive care patients, it is complicated by the re-aspiration of bacteria that accumulate above the cuff of the intubation tube. Identification of nosocomial and community-acquired pneumonia involves a particular flora of pathogens and, accordingly, involves empiric therapy. Routine analysis of sputum according to Gram gives approximate data, which is a clarification for empiric treatment. We present a clinical case, which demonstrates that infection is also possible due to contact of a family member with another one, working at a medical institution. Therefore, in our clinical case, we emphasize that it is very important to collect a thorough history. Careful collection of medical history can provide additional information: working in a team, being a medical professional, relatives working at a medical institution. It should be noted that in this category of patients, the causative agent of infection, including nosocomial pneumonia, may be the strains of nosocomial microorganisms. Regardless of age, we recommend the use of preventive measures (lifestyle modification, acclimatization training, sports, etc.) to increase the non-specific resistance of the body. As a preventive measure, medical personnel should follow the regimes of ventilation and wet cleaning in the premises, wash their hands and rinse their nasal passages as often as possible with saline solutions, use a mask to protect the respiratory organs, disinfect hands with alcohol.